2020
DOI: 10.1101/2020.06.15.136937
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Spindle scaling is governed by cell boundary regulation of microtubule nucleation

Abstract: Cellular organelles such as the mitotic spindle adjust their size to the dimensions of the cell. It is widely understood that spindle scaling is governed by regulation of microtubule polymerization. Here we use quantitative microscopy in living zebrafish embryos and Xenopus egg extracts in combination with theory to show that microtubule polymerization dynamics are insufficient to scale spindles and only contribute below a critical cell size. In contrast, microtubule nucleation governs spindle scaling for all … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 64 publications
(92 reference statements)
0
8
0
Order By: Relevance
“…, 2013 ; Rieckhoff et al. , 2019 , 2020 ). Second, while most MAPs that slow down depolymerization have been reported to accelerate polymerization in minimal conditions ( Drechsel et al.…”
Section: Discussionmentioning
confidence: 99%
“…, 2013 ; Rieckhoff et al. , 2019 , 2020 ). Second, while most MAPs that slow down depolymerization have been reported to accelerate polymerization in minimal conditions ( Drechsel et al.…”
Section: Discussionmentioning
confidence: 99%
“…It was suggested that these flows can arise from the high degree of connectivity introduced by molecular motors. However, in contrast to stabilized mixtures, microtubules in the spindle are constantly nucleated throughout the structure ( Oh et al, 2016, Decker et al, 2018, Rieckhoff et al, 2020 ) and turnover rapidly ( Brugués et al, 2012, Redemann et al, 2017, Rieckhoff et al, 2020 ). In particular, microtubule nucleation is an auto-catalytic process ( Ishihara et al, 2014, Oh et al, 2016, Decker et al, 2018 ), which leads to microtubule structures that are genuinely different from the ones obtained in other simplified in vitro systems ( Sanchez et al, 2012, Roostalu et al, 2018, Fürthauer et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, the EB1 C-terminal half could interfere with cortical MT capture, although mCherry-Zdk1-EB1C does not localize to the cortex in blue light. Notably, although MT growth has been linked to spindle length [29,30], π-EB1 photoinactivation-mediated spindle shortening was not accompanied by a MT growth rate decrease. Instead, we think that acute EB1 inhibition causes an imbalance of forces acting on the spindle poles that actively drives spindle shortening.…”
Section: Resultsmentioning
confidence: 99%